PEMANFAATAN MEDIA INSTAGRAM SEBAGAI KNOWLEDGE SHARING PEMBUATAN MENU MAKANAN SEHAT - Hidayah, Debby Ummul; Lestari, Puji; Kasih, Dwifa Julieta; Nurhayati, Septi (Universitas Sanata Dharma, 2024)
Choosing a healthy food menu is very important to maintain daily health. Especially for young children, fulfilling balanced nutrition must be based on a healthy diet. Because it will have an impact on the child's growth and development. However, in practice, there are still many parents who do not understand well about choosing a healthy food menu. Therefore, one solution that can be provided is to provide training in making healthy food menus. This community service is aimed at parents or guardians of students from Bustanul Athfal Rabak Kindergarten. The application of Instagram social media can also be used as a tool to help solve problems. This Instagram media is considered effective for sharing knowledge about healthy food menus. So parents use Instagram media to look for healthy menu recipes and try to apply the recipes given. The method applied in this community service activity is direct lectures and training using the Instagram application to access recipes for healthy food menus and direct practice in making healthy food menus. The results are that students or parents can use Instagram to search for healthy food menu recipes and understand how to make healthy food menu recipes.